2009
DOI: 10.2136/sssaj2007.0184
|View full text |Cite
|
Sign up to set email alerts
|

Organic Matter and Water Stability of Field Aggregates Affected by Tillage in South Dakota

Abstract: Tillage has been associated with soil organic matter (SOM) decline. A case study of two adjacent farms was conducted in eastern South Dakota. One farm used no‐till (NT) and the other used chisel tillage (CT). We hypothesized that soil under NT, compared with tillage, would have both greater quantity and greater quality of SOM and that this improved SOM condition would result in increased water stable aggregation (WSA). A rotary sieve was used to sort dry field aggregates into six size groups: <0.4, 0.4 to 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
37
1
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 59 publications
5
37
1
3
Order By: Relevance
“…Water stable soil aggregates presented higher values under NT (59%) than CT treatment (32%) ( Figure 2A); these results are in accordance with previous studies (Castro Filho et al, 2002;Martínez et al, 2008;Pikul et al, 2009). There are various evidences in relation to the fact that the CT management produces a decrease in the soil aggregation due to mechanical effects or by destruction of the network of AMF fungal mycelium (Alvaro-Fuentes et al, 2008;Six et al, 1999;Wright and Upadhyaya, 1998).…”
Section: Resultssupporting
confidence: 92%
“…Water stable soil aggregates presented higher values under NT (59%) than CT treatment (32%) ( Figure 2A); these results are in accordance with previous studies (Castro Filho et al, 2002;Martínez et al, 2008;Pikul et al, 2009). There are various evidences in relation to the fact that the CT management produces a decrease in the soil aggregation due to mechanical effects or by destruction of the network of AMF fungal mycelium (Alvaro-Fuentes et al, 2008;Six et al, 1999;Wright and Upadhyaya, 1998).…”
Section: Resultssupporting
confidence: 92%
“…Positive effects of no-till on soil health parameters have been widely documented and include major reductions in soil erosion and fuel consumption, reduced CO 2 emissions, and enhanced water quality, biological activity, soil fertility and production stability (Pretty 2008;Derpsch et al 2010;Lafond et al 2011 and references therein). Studies in the NGP have also reported better soil aggregation, enhanced soil organic C, and increased potentially mineralizable N in no-till soils (McConkey et al 2003;Liebig et al 2004;Pikul et al 2009;Malhi et al 2009;Lafond et al 2011). Microbial biomass, especially of mycorrhizal fungi, is often, but not always, greater in no-till soils (Liebig et al 2004;Helgason et al 2010;Monreal et al 2011); soil organism community structure may also be different in no-till than tilled soils (Helgason et al 2010).…”
Section: Reducing Tillagementioning
confidence: 99%
“…Soil for dry aggregate size distribution was collected in the summer of 2011 within about 5 cm of the soil surface after removing visible surface residue. Dry aggregate size distribution using the method described by Chepil [39] and Pikul et al [40] was determined using a rotary sieve operating at 6-rpm to separate air-dried soil into six aggregate size groupings: 0-0.5, 0.5-1.0, 1-2, 2-3, 3-5, 5-9, and 9-20 mm. Total soil mass in aggregates <20 mm and mass of each aggregate size was determined.…”
Section: Soil Parametersmentioning
confidence: 99%